Effects of Clostridium butyricum and sodium butyrate on growth performance, immunity, and gut microbiota of mirror carp Cyprinus carpio fed with soybean meal based diet - Du, Yi; Cheng, Long; Zhao, Jianhua; de Cruz, Clement R.; Xu, Hong; Wang, Liansheng; Xu, Qiyou (Elsevier BV, 2023)
This study investigated the effects of Clostridium butyricum (CB) and sodium butyrate (SB) on the growth performance, intestinal immune, and gut microbiota of mirror carp (Cyprinus carpio) fed with a high level of soybean meal. Three hundred sixty healthy carp fingerlings (∼3.74 g) were divided into eight dietary treatments with four replicates and ten fish per replicate. Which include basal diet (Control group, C0); C0 supplemented with three levels of CB, 3 × 107 cfu/kg (C1), 3 × 108 cfu/kg (C2), 3 × 109 cfu/kg (C3); three levels of SB, 500 mg/kg (S1), 1000 mg/kg (S2), 2 000 mg/kg (S3); and 3 × 108 cfu/kg CB+ 1 000 mg/kg SB (CS), respectively. In 8-week trial, the survival rate of all groups was 100%. Compared with C0, the Weight Gain, Feed Conversion Ratio, Protein Efficiency Ratio were not significantly different in all groups (P > 0.05). Crude protein and ether extract contents were increased significantly (P < 0.05) when supplemented with different levels of CB and SB, and ash content increased significantly in the CB groups (P < 0.05). Serum globulin increased and glucose decreased significantly (P < 0.05) in the CB and SB groups. The intestinal T-SOD and glutathione activity in the foregut, midgut, and hindgut were increased (P < 0.05), and villus height of foregut and midgut were higher in the CB and SB (P < 0.05). Protease activities in the foregut and midgut were significantly increased (P < 0.05) in the C2, C3, S2, and S3. The lipase activity of the C2 and C3 in foregut, midgut, and hindgut; S2, S3, and CS in the foregut; S3 in midgut were significantly increased (P < 0.05). The gut microbiota was modulated at the phylum and genera level by CB and SB administration. In summary, our results indicated that CB and SB could promote the whole body CP and EE content, intestine immunity, digestive enzyme activity, and intestinal morphology, and modulated gut flora in carp.